2016
DOI: 10.1016/j.exphem.2016.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-like growth factor 2 modulates murine hematopoietic stem cell maintenance through upregulation of p57

Abstract: Hematopoietic stem cells (HSC) rely on a highly regulated molecular network to balance self-renewal and lineage specification to sustain life-long hematopoiesis. Despite a plethora of studies aimed at identifying molecules governing HSC fate, our current knowledge of the genes responsible is limited. We have found Insulin-like growth factor 2 (IGF2) to be predominantly expressed within long-term HSC. This study examines IGF2 expression patterns and the effects of the gene in HSC. Through the overexpression and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 58 publications
1
29
0
Order By: Relevance
“…Conversely, Igf2 overexpression would boost HSC progression into the cell cycle, leading to proliferation with a risk of exhaustion of the HSC pool on the long term. The data of Thomas et al 2016 show that in this situation p57 increases and limits the progression of HSC through the cell cycle, preserving the HSC pool and a better repopulation capacity. Our two studies suggest that p57 would counterbalance the effects of Igf2 on the HSC pool in order to protect it.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, Igf2 overexpression would boost HSC progression into the cell cycle, leading to proliferation with a risk of exhaustion of the HSC pool on the long term. The data of Thomas et al 2016 show that in this situation p57 increases and limits the progression of HSC through the cell cycle, preserving the HSC pool and a better repopulation capacity. Our two studies suggest that p57 would counterbalance the effects of Igf2 on the HSC pool in order to protect it.…”
Section: Discussionmentioning
confidence: 99%
“…To further explore the nature of this developmental transition, we searched for DEGs that were concurrently downregulated in all stromal lineages in adult compared to juvenile BM. We found a unique signature containing only seven common genes, which includes Ptn, Igf2 and Dlk1, genes that are known to play decisive roles in the regulation of self-renewing expansion of adult and embryonic (Chou and Lodish, 2010;Himburg et al, 2018;Kokkaliaris et al, 2016;Mascarenhas et al, 2009;Thomas et al, 2016) HSCs . Strikingly, all seven genes displayed by far the highest expression levels in juvenile PαSc compared to other stromal subsets, and the majority (four out of seven, Igf2, Dlk1, Peg3 and Mest) belong to a group of genomically imprinted genes, which are monoallelicaly expressed in a parent of origin-specific fashion ( Figure 4E).…”
mentioning
confidence: 89%
“…Among them, IGF2 is a mitogenic factor for HSCs, which is produced by putative niche cell types of the fetal liver (Chou and Lodish, 2010;Mascarenhas et al, 2009;Thomas et al, 2016;Wu et al, 2008).…”
mentioning
confidence: 99%
“…Culturing hematopoietic stem cells with IGF2 increases the number of both multilineage colonies and hematopoietic stem cells (Zhang & Lodish ; Thomas et al . ). We also found that 12.5, 14.5 and 16.5 dpc liver hepatoblast‐like cells highly express Igf2 mRNA (Figs S2–S4 in Supporting Information).…”
Section: Discussionmentioning
confidence: 97%
“…Taken together, hepatic stellate cells likely function as hematopoietic niche through Igf2 secretion. IGF2 is expressed in long-term hematopoietic stem cells and produced by 15 dpc Ter119-CD3+ fetal liver cells (Zhang & Lodish 2004;Thomas et al 2016). Culturing hematopoietic stem cells with IGF2 increases the number of both multilineage colonies and hematopoietic stem cells (Zhang & Lodish 2004;Thomas et al 2016).…”
Section: 82mentioning
confidence: 99%